Integrasi Nilai Islami dalam Manajemen Pendidikan Anak Usia Dini: Pendekatan Permainan di TK Aisyiyah Kedunggudel - Budi Sunariyanto; Agus Sriyanto; Elyaum Farihah; Alan Lutfi Gesang Saputra (IAIN Datuk Laksemana Bengkalis, Indonesia, 2025)
This study aims to examine the integration of Islamic values into early childhood education management through a play-based approach at TK Aisyiyah Kedunggudel. The research used a qualitative case study method. Data were collected through in-depth interviews, observations, and documentation. The findings show that Islamic games such as asmaul husna cards, prayer movement guessing, and prophetic story drama effectively instill values of honesty, responsibility, empathy, and love for Allah and the Prophet. These games are systematically integrated into the daily lesson plans and supported by structured management, including value documentation through children's portfolios. Islamic play also significantly enhances children’s spiritual and social intelligence. However, challenges remain, such as limited game media and teachers’ skills in designing contextual games. The study recommends strengthening teacher capacity and developing an Islamic play-based curriculum to improve the overall quality of early childhood education management.